К физическим основам информационной коррекции погоды - Рокитянский, И.И. (Геоінформатика, 2014)
Воздействие на погоду путем посылки активного мысленного намерения введено в категорию информационных воздействий. Показано, что оно может осуществляться в соответствии с законами физики. Информационные воздействия реализуются в зонах неустойчивости в точках бифуркации, систематически или спорадически возникающих в отдельных частях метеорологической системы. Вплив на погоду через посилання активного мисленного наміру введено в категорію інформаційних впливів. Показано, що він може здійснюватися відповідно до законів фізики. Інформаційні впливи реалізуються в зонах нестійкості в точках біфуркації, що систематично або спорадично виникають в окремих частинах метеорологіч¬ної системи. Weather correction by technological methods is feasible but its effectiveness is rather low. Meanwhile, there is a huge amount of evidence on all continents and in all historical times, including today, that individuals or groups of people by means of mental impulse, magic ritual or, prayer can change the weather at will. This method will be called informational weather correction, and it works in accordance with physical laws. To substantiate this assertion the author uses mathematical works of J.H. Poincare and E.N. Lorenz devoted to deterministic chaos, physical works of D. Nicolis and B.B. Kadomcev on the dynamics of hierarchical systems, and natural philosophy works of V.I. Vernadsky, S. Grof and K.G. Jung on the noosphere and collective unconscious. Informational weather correction can be realized in unstable zones in bifurcation points, which systematically arise in some parts of meteorological system.